Gravity assisted reduction of ankle (GARA) fractures: Results of a novel technique for relocating displaced ankle fractures in the emergency setting in comparison to traditional manipulation and reduction (TMR) technique. Issue 7 (October 2022) - Rangan, Raghunaathan; Mohammed, Riaz; Fenton, Paul Andrew; Bose, Deepa
Abstract: Background: Ankle fracture displacements cause significant discomfort to the patient and can compromise soft tissues including the neurovascular structures. Prompt reduction and plaster splint application are vital in the early management of these potentially limb-threatening conditions. The process can be distressing for the patient often requiring additional personnel or equipment. We have used a novel technique of Gravity Assisted Reduction of Ankle (GARA) fractures and compared the results with the Traditional Manipulation and Reduction (TMR) technique. Material and methods: With adequate analgesia, the patient turns to lay either in lateral or prone position depending on fracture pattern, thus permitting gravity to gradually aid in reduction and hold the fracture in place while Plaster Of Paris (POP) is applied. We performed a retrospective comparative study of GARA vs TMR using validated radiological parameters to assess the quality of reduction with both techniques. Results: 21 patients had GARA technique, in comparison with 19 patients in TMR group. All measured radiological parameters showed similar improvement in both the groups, despite the fact that the pronation-external rotation injury pattern was more often seen in the GARA group. Intravenous sedation and monitoring were needed in 10 patients of TMR group, none in GARA group. On an average 4 personnel needed for TMR, but only 2 personnel needed for GARA technique. Conclusion: Gravity assisted ankle fracture reduction is a simple, effective and reproducible alternative technique to TMR, with no need of intravenous sedation along with fewer people needed to perform the procedure. Level of evidence: 3b